Influence of Incorporation of Natural Fibers on the Physical, Mechanical, and Thermal Properties of Composites LDPE-Al Reinforced with Fique Fibers - Miguel A. Hidalgo-Salazar; Mario F. Muñoz; José H. Mina (International Journal of Polymer Science)
This study shows the effect of the incorporation of natural fique fibers in a matrix formed by low-density polyethylene and aluminum (LDPE-Al) obtained in the recycling process of long-life Tetra Pak packaging. The reinforcement content was 10, 20, and 30% fibers, manufactured by hot-press compression molding of composite boards (LDPE-Al/fique). From the thermogravimetric analysis (TGA) it was determined that the proportions of the LDPE-Al were 75 : 25 w/w. Likewise, it was found that the aluminum particles increased the rigidity of the LDPE-Al, reducing the impact strength compared to LDPE recycled from Tetra Pak without aluminum; besides this, the crystallinity in the LDPE-Al increased with the presence of aluminum, which was observed by differential scanning calorimetry (DSC). The maximum strength and Young’s modulus to tensile and flexural properties increased with the incorporation of the fibers, this increase being a direct function of the amount of reinforcement contained in the material. Finally, a reduction in the density of the compound by the generation of voids at the interface between the LDPE-Al and fique fibers was identified, and there was also a greater water absorption due to weak interphase fiber-matrix and the hydrophilic fibers contained in the material.